2002
DOI: 10.1128/mcb.22.21.7593-7602.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Mitogen-Activated Protein Kinase Kinase Activation Domain Recognized by the Inhibitor PD 184352

Abstract: Utilizing a genetic screen in the yeast Saccharomyces cerevisiae, we identified a novel autoactivation region in mammalian MEK1 that is involved in binding the specific MEK inhibitor, PD 184352. The genetic screen is possible due to the homology between components of the yeast pheromone response pathway and the eukaryotic Raf-MEK-ERK signaling cascade. Using the FUS1::HIS3 reporter as a functional readout for activation of a reconstituted Raf-MEK-ERK signaling cascade, randomly mutagenized MEK variants that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…A complete set of mutant MEK1 alleles and the methods of identification are listed in Table S1. This combined analysis of Ϸ1,100 resistant clones vastly exceeded the scope of prior mutagenesis studies (14) and offered a comprehensive framework for unbiased characterization of MEK1-mediated drug resistance.…”
Section: Comprehensive Identification Of Mek1 Resistance Mutations Inmentioning
confidence: 99%
“…A complete set of mutant MEK1 alleles and the methods of identification are listed in Table S1. This combined analysis of Ϸ1,100 resistant clones vastly exceeded the scope of prior mutagenesis studies (14) and offered a comprehensive framework for unbiased characterization of MEK1-mediated drug resistance.…”
Section: Comprehensive Identification Of Mek1 Resistance Mutations Inmentioning
confidence: 99%
“…Previous studies have also reported multiple JAK2 inhibitors that maintained or increased the phosphorylation levels of JAK2 (44,45). In addition, inhibitors for other kinases have been shown to not affect the phosphorylation levels of the target kinase, whereas the activity was inhibited by the compounds (51)(52)(53). A possible explanation might be that a negative feedback pathway occurs after inhibition of JAK2 such that a hyperactivated upstream kinase could increase the phosphorylation level.…”
Section: Discussionmentioning
confidence: 93%
“…The successful development of MEK inhibitors may be due to the relatively few phosphorylation sites on MEK involved in activation/inactivation. MEK inhibitors differ from most other kinase inhibitors as they do not compete with ATP binding which confers a very high specificity (Delaney et al, 2002). MEK inhibitors are very specific and do not inhibit many different protein kinases including p38 MAPK and JNK (Davies et al, 2000).…”
Section: Therapeutic Targeting Of the Pi3k/akt/pten/mtor And Raf/mek/mentioning
confidence: 99%